CD38+ CD58− is an independent adverse prognostic factor in paediatric Philadelphia chromosome negative B cell acute lymphoblastic leukaemia patients. (April 2016) - Li, Xu-Mian; Zhang, Le-Ping; Wang, Ya-Zhe; Lu, Ai-Dong; Chang, Yan; Zhu, Hong-Hu; Qin, Ya-Zhen; Lai, Yue-Yun; Kong, Yuan; Huang, Xiao-Jun; Liu, Yan-Rong
Highlights: Ph− B-ALL patients with CD38+ CD58− have a higher relapse rate and shorter survival. A higher risk population of Ph− B-ALL patients with CD38+ CD58- was identified. A method for better risk stratification was proposed in Ph− B-ALL patients. Abstract: To explore new risk predictors for a high risk of relapse in Philadelphia chromosome negative (Ph−) B cell acute lymphoblastic leukaemia (B-ALL) patients, 196 paediatric Ph− B-ALL patients (≤18 years) were retrospectively analysed. We mainly focus on investigating the prognostic value of CD38 and CD58 expression in leukemic blasts in these patients by four colour flow cytometry. The CD38+ CD58− group ( n  = 16) had a higher relapse rate, a shorter 3-year event-free survival (EFS) and overall survival (OS) than the CD38+ CD58+ group ( n  = 157; 31.3% vs 10.2%, P  = 0.04; 52.4% vs 92.3%, P  < 0.01; 32.5% vs 91.0%, P  = 0.01); CD38+ CD58− was an independent adverse prognostic predictor for relapse (hazard ratio [HR], 0.203; 95%CI, 0.063–0.656; P  = 0.01), 3-year EFS (HR, 0.091; 95%CI, 0.023–0.355; P  < 0.01) and OS (HR, 0.102; 95%CI, 0.026–0.3971; P  < 0.01) in this cohort, as determined by Cox multivariate analysis. We identified, for the first time, a higher risk population of paediatric Ph− B-ALL patients with CD38+ CD58− who had a higher relapse risk and a shorter survival. Our results may allow better risk stratification and individualized treatment.